Pengaruh Komunikasi, Kepemimpinan dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan pada PT. Putra Mas Pratama - Laurensia Florentina; Hendry Hendry; Caroline Margaretha Samsul; Roza Milasari (IPM2KPE, 2023)
This research is based on a decline in employee job satisfaction which is marked by an increase in employee resignations caused by communication factors, leadership factors and work discipline factors. Quantitative descriptive research method. The population in this study were all employees of PT Putra Mas Pratama Medan, totaling 131 employees. The number of samples in this research was 99 employees. Data collection uses questionnaires, interviews and documentation. The data analysis technique uses multiple linear regression analysis. Conclusion, partially Communication has a positive and significant effect on Employee Job Satisfaction, partially Leadership has a positive and significant effect on Employee Job Satisfaction and partially Work Discipline has a positive and significant effect on Employee Job Satisfaction and simultaneously Communication, Leadership and Work Discipline have a positive and significant effect on Employee Job Satisfaction. Keywords: Work Discipline, Leadership, Employee Job Satisfaction, Communication